Quality management school, Symposium of Industrial Engineering ,Maintenence School - Todorović, Jovan (Journal of Applied Engineering Science, 2011)
Considering business conditions of European market, quality has a signifi cant role, not only in providing new markets, but also in maintaining the existing ones. Nowadays, customers do not only expect a quality product, but they require a proof that the company is capable to produce high quality products and provide quality services. Obtaining of this evidence should be the fi rst goal for each company that has high aspirations when it comes to new markets but also standard’s procedure in order to maintain its reputation. Implementation is not complete if employees are not familiar with standards.With the aim to closer inform the employees of the meaning and signifi cance of ISO standards, Institute for research and design in commerce & industry – IIPP organize training “School of Quality”.